Evaluation of Analytical and Clinical Performance and Usefulness in a Real-Life Hospital Setting of Two in-House Real-Time RT-PCR Assays to Track SARS-CoV-2 Variants of Concern - Alice Moisan; Anaïs Soares; Fabienne De Oliveira; Elodie Alessandri-Gradt; François Lecoquierre; Steeve Fourneaux; Jean-Christophe Plantier; Marie Gueudin (Viruses, 2023)
Since the end of 2020, multiple severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) have emerged and spread worldwide. Tracking their evolution has been a challenge due to the huge number of positive samples and limited capacities of whole-genome sequencing. Two in-house variant-screening RT-PCR assays were successively designed in our laboratory in order to detect specific known mutations in the spike region and to rapidly detect successively emerging VOCs. The first one (RT-PCR#1) targeted the 69–70 deletion and the N501Y substitution simultaneously, whereas the second one (RT-PCR#2) targeted the E484K, E484Q, and L452R substitutions simultaneously. To evaluate the analytical performance of these two RT-PCRs, 90 negative and 30 positive thawed nasopharyngeal swabs were retrospectively analyzed, and no discordant results were observed. Concerning the sensitivity, for RT-PCR#1, serial dilutions of the WHO international standard SARS-CoV-2 RNA, corresponding to the genome of an Alpha variant, were all detected up to 500 IU/mL. For RT-PCR#2, dilutions of a sample harboring the E484K substitution and of a sample harboring the L452R and E484Q substitutions were all detected up to 1000 IU/mL and 2000 IU/mL, respectively. To evaluate the performance in a real-life hospital setting, 1308 and 915 profiles of mutations, obtained with RT-PCR#1 and RT-PCR#2, respectively, were prospectively compared to next-generation sequencing (NGS) data. The two RT-PCR assays showed an excellent concordance with the NGS data, with 99.8% for RT-PCR#1 and 99.2% for RT-PCR#2. Finally, for each mutation targeted, the clinical sensitivity, the clinical specificity and the positive and negative predictive values showed excellent clinical performance. Since the beginning of the SARS-CoV-2 pandemic, the emergence of variants—impacting the disease’s severity and the efficacy of vaccines and therapies—has forced medical analysis laboratories to constantly adapt to the strong demand for screening them. Our data showed that in-house RT-PCRs are useful and adaptable tools for monitoring such rapid evolution and spread of SARS-CoV-2 VOCs.